Strengthening Corporate Cash Holdings and Investment Efficiency in the COVID-19 Pandemic: Some Empirical Evidence from Indonesia Emerging Markets - Suham Cahyono; Ardianto Ardianto (Institute of Research and Community Outreach - Petra Christian University, 2024)
This study explores the connection between the amount of cash a company holds and its effectiveness in making investments, as well as the effect of the COVID-19 pandemic. The researchers analyzed a dataset consisting of 2721 observations from Indonesian publicly listed firms between 2013 and 2020, excluding the financial industry (SIC 6). They utilized multiple linear regression analysis to investigate how cash holding influences investment efficiency and how the COVID-19 pandemic affects this relationship. The research approach employed was quantitative. The results indicate that a higher cash holding has a negative impact on investment efficiency. The uncertainty caused by the COVID-19 outbreak has significantly affected corporate cash flows, impeding business activities. Additionally, robustness tests were conducted to address concerns regarding potential bias, and the results consistently aligned with the ordinary least squares (OLS) estimation. These findings are significant for investors, potential investors, and management, providing insights into the interplay among cash holding, investment efficiency, and the COVID-19 Pandemic.